Permanency : Situating formalization of informal settlements in the City of Tshwane, South Africa - (:unkn) unknown (My University, 2021)
This study seeks to rethink the place of informal spaces in the sustainability and environmental governance discourses in South Africa through a critical and southern theory lens. There is no doubt that the urban sustainability paradigm has become a growing concern in urban governance. Various global environmental governance logics such as the Sustainable Development Goals (the SDGs), most notably the SDG11, have elevated the significance of informality in this urban sustainability agenda, with their calls for interventions to address the poor living environments facing informal settlements (UNHabitat). An interesting observation is that while urban informality has come to occupy a prominent position in urban sustainability narratives and governance, informality continues to be regarded as an antithesis of sustainability. The rise of formalization as a process of production of subaltern spaces in cities such as Tshwane, has put a spotlight on these politics of urban environmental governance. There have been some advances to question what (Myers, 2008) frames as a “disconnection between sustainable urban development and environmental justice in sub-Saharan African cities” (p:705). Some scholars, including Patel (2009), have also started to question the absence of environmental justice objectives in sustainability policies. Nevertheless, there remain a dearth of studies interrogating how the contradicting governance rationalities of urban sustainability and environmental justice intersect in local urban governance discourses in the global South. To fill this gap, I lean on Urban Political Ecology and southern theory to help analyze how such modes underpin the continued environmental injustices in informal spaces. To concretize this argument, I embark on analyzing an ‘embedded case study’ (Lin, 1993) of the formalization of informal settlements in the City of Tshwane. Through this case, I show that, although formalization emerged as a housing poli
Keywords: African Research